Stand Structure and Above-ground Biomass of Two Tree Plantations at Bharathiar University, Coimbatore - Karthick, A.; Arul Pragasan, L. (Indian Forester, 2014)
This study aims to determine the stand density, basal area and above-ground biomass (AGB) of two plantations, Eucalyptus plantation (EP) and mixed species plantation (MP) in the campus of Bharathiar University, Coimbatore -1 -1 (Tamil Nadu), India. Tree density was high at the site MP i.e. 468 stems ha than site EP (320 stems ha ). Whereas, in 2 -1 case of basal area, the fast growing Eucalyptus tree plantation site had greater value 9.42 (± 0.15) m ha than site MP 2 -1 -1 8.67 (± 0.11) m ha . Also, site EP had greater AGB value 41.78 tonne ha (± 0.7 SD) when compared to the mixed -1 plantation which had 34.47 tonne ha (± 0.52 SD). However, T-test showed that there was no significant difference in AGB (t = 0.131, P < 0.05), density (t = 0.005, P < 0.05) as well as basal area (t = 0.297, P < 0.05) between the two study sites. There was a positive correlation (p > 0.05) between AGB with tree density and basal area at both sites. When compared, AGB of the present study falls within the range reported worldwide.